The influence of short stature on affected person’s life - Zieniewicz, Hubert (Current Problems of Psychiatry, 2011)
Western civilization has fostered tall and slim people for many years, the evident manifestation of which is their definite domination in mass culture area. Tall stature is a synonym of authority and success in social consciousness. Stereotypes of short stature are strong enough to storm medical environment. In a last few years short stature has become a medical problem, so even normal short stature children are hormonally treated today. Many scientists indicated negative influence of short stature on child’s psychosocial development. In their studies they were proving that short children, both healthy and endocrinologically ill, significantly differ from average stature children. Results of their studies have been questioned. They are reproached for serious methodological defects that led to artifacts about real influence of short stature per se on affected person’s life. Correlation: short stature – life success is neither strong nor straight. It depends on many biological, psychical and socio–economical factors. This article analyzes influence of short stature on affected person’s life, taking into account: factors of illness, reactions of social environment, reactions of the family and dimensions of development.